2006
DOI: 10.1074/jbc.m604504200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Protein Kinase Cδ in Platelet Signaling, αIIbβ3 Activation, and Thromboxane A2 Release

Abstract: The protein kinase C (PKC) family is an essential signaling mediator in platelet activation and aggregation. However, the relative importance of the major platelet PKC isoforms and their downstream effectors in platelet signaling and function remain unclear. Using isolated human platelets, we report that PKC␦, but not PKC␣ or PKC␤, is required for collagen-induced phospholipase C-dependent signaling, activation of ␣ IIb ␤ 3 , and platelet aggregation. Analysis of PKC␦ phosphorylation and translocation to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 48 publications
2
83
0
1
Order By: Relevance
“…These data indicate that in platelets the stimulatory effects of PKC are regulated in a more distinct way than the suppressive effects of PKC, and they suggest that the latter are mediated by one or more nonclassical PKC isoforms. Mechanistically, these effects of Gö6976 are well explained by the recent observation that PKC␣ has a negative regulatory effect on Src kinases (45), the activity of which is of key importance in GPVI-induced signal transduction (23), although other authors propose that PKC␦ is required for collagen-induced phospholipase C activation (47). In HEK293 and COS1 cells, PKC␣ is recognized as a quickly responding element to local elevation in [Ca 2ϩ ] i (48).…”
Section: Discussionmentioning
confidence: 83%
“…These data indicate that in platelets the stimulatory effects of PKC are regulated in a more distinct way than the suppressive effects of PKC, and they suggest that the latter are mediated by one or more nonclassical PKC isoforms. Mechanistically, these effects of Gö6976 are well explained by the recent observation that PKC␣ has a negative regulatory effect on Src kinases (45), the activity of which is of key importance in GPVI-induced signal transduction (23), although other authors propose that PKC␦ is required for collagen-induced phospholipase C activation (47). In HEK293 and COS1 cells, PKC␣ is recognized as a quickly responding element to local elevation in [Ca 2ϩ ] i (48).…”
Section: Discussionmentioning
confidence: 83%
“…The serine/threonine kinases known to be activated in platelets in response to ADP and thrombin are PKCs, including PKC␦ (20,21), PKB/Akt, a downstream kinase of phosphatidylinositol 3-kinase (PI3K) (22)(23)(24), PKD, a PI3K and PKC-dependent kinase (25), and GSK3, which is also PI3K-dependent (26). Treatment of platelets with the PI3K inhibitors wortmannin or LY294002 did not affect levels of Rap1GAP2 serine 9 phosphorylation (Fig.…”
Section: Kinases Involved In Rap1gap2 Serine 9 Phosphorylation-mentioning
confidence: 95%
“…TXA 2 is released as a positive feedback mediator when platelets are activated by physiological agonists such as thrombin, ADP, and 5-HT. 18,19) It has been shown that a TXA 2 receptor antagonist partially inhibits platelet aggregation induced by thrombin or ADP. 20,21) Therefore it is assumed that the 100% ethanol extract can inhibit platelet aggregation partially induced by other stimulants except a TXA 2 receptor agonist.…”
Section: Discussionmentioning
confidence: 99%